A retrospective analysis of the effects of COVID-19 on cancer diagnosis and staging in Taiwan - Chen, Chien-Chih; Cheng, Hao-Shen; You, Weir-Chiang; Yeh, Hui-Ling; Wang, Lily; Chao, Jeffrey; Liu, Yi-Chun; Huang, Jing-Wen; Hsieh, He-Yuan; Li, Chuan (The Journal of Infection in Developing Countries, 2026)
Introduction: This study aimed to evaluate the psychological and behavioral impacts of the coronavirus disease-2019 (COVID-19) pandemic on cancer diagnosis and staging, with particular focus on patient delays and changes in healthcare-seeking behavior before and after the onset of COVID-19. Methodology: Data pertaining to 8 cancer types, including breast cancer, hepatocellular carcinoma, oral cancer, prostate cancer, gastric cancer, esophageal cancer, colon cancer, and lung cancer, sourced from the cancer registry database of Taichung Veterans General Hospital, was analyzed. The focus was on the comparisons of data between the pre-pandemic period (2017–2019) and the pandemic year (2020). Results: Breast cancer (p < 0.001), hepatocellular carcinoma (p = 0.004), prostate cancer (p < 0.001), gastric cancer (p = 0.037), and esophageal cancer (p < 0.001) exhibited a decrease in the rate of early stage patients and an increase in the rate of advanced stage patients after the COVID-19 outbreak. Furthermore, the number of newly diagnosed patients per year decreased for hepatocellular carcinoma, oral cancer, prostate cancer, gastric cancer, esophageal cancer, colon cancer, and lung cancer. Conclusions: The COVID-19 pandemic disrupted cancer care, resulting in delayed diagnoses, stage migration, and a decline in newly diagnosed cases. These findings highlight the need for resilient healthcare systems to ensure continuity of cancer screening and treatment during global health crises.